Preliminary Advice on Fruit Handling, Seed Pretreatment and 'Germination' of Embryos of Prumnopitys andina - Gosling, Peter; Ives, Lorelie M; Cunningham, Victoria J; Hechenleitner Vega, Paulina; Brownless, Peter; Thomas, Philip; Martinez, Camila (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2005)
Prumnopitys andina is a member of the Podocarpaceae native to Chile and Argentina. It is known to be relatively easy to propagate vegetatively, but germination from seeds is poor and can be spread over at least four years. This paper describes the methods that were used to raise 89 seedlings from 262 seeds (=34%) in less than 1 year. The sequence involves i) completely removing the fleshy sarcotesta; ii) thoroughly washing the seed-coat; iii) `pretreating' the imbibed seeds by incubating them in moist peat and sand at a daily alternating 10/15°C for several months (to allow 'maturation' or `after-ripening' / 'dormancy breakage' at present we do not know which); iv) carefully cracking the seed-coat in a vice and extracting the embryo; v) culturing clean, firm, healthy (=-`viable') embryos on moist filter paper at a daily alternating 20/30°C (with lights during the 30°C phase); [vi) where necessary, freeing the cotyledons of all seedlings that become trapped in the female gametophyte]; vii) transplanting seedlings to conventional nursery practice. A further 1008 seeds are continuing 'pretreatment' to investigate whether this will increase the proportion of seedlings per viable embryo or better still lead to a much less labour intensive seedling emergence from intact seeds.